THE ROLE OF BRAND COMMUNITY IDENTIFICATION IN INCREASING RELIGIOUS VALUE CO-CREATION AND CUSTOMER STICKINESS - MA Irfan Rahmana; Bahrain Pasha Irawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to examine the role of Religious Brand Community Identification which is strengthened by Customer Participation in increasing Religious Value co-Creation and Customer Stickiness for religiocentric consumers. As many as 285 respondents were consumers who were involved in the process of purchasing syar'I clothing via an online shop. Structural Equation Model (SEM) is used to analyze data and test empirical models. This study succeeded in proving the role of Religious Brand Community Identification driven by Customer Participation in increasing the intensity of carrying out Religious Value co-Creation and Customer Stickiness. The results of this study can be used by online shops that offer religion-based products to manage the religiocentric market more seriously by consistently strengthening syar'i clothing brands with Islamic values through consumer involvement in sharing knowledge and religious beliefs related to the use of syar'i clothing. . Consumer involvement in strengthening religion-based brands in a virtual community has proven to be a brand glue and a solid barrier against the entry of non-syar'i products. This can be a reason for online shop owners to stick to religious values when designing and offering syar'i clothing. If this causal relationship can be carried out consistently, it will further strengthen the halal ecosystem. This can be a reason for online shop owners to stick to religious values when designing and offering syar'i clothing. If this causal relationship can be carried out consistently, it will further strengthen the halal ecosystem. This can be a reason for online shop owners to stick to religious values when designing and offering syar'i clothing. If this causal relationship can be carried out consistently, it will further strengthen the halal ecosystem. Keyword:Religious Brand Community Identification, Customer Participation, Religious Value co-Creation, Customer Stickiness, Religiocentric.